Effectiveness of Acupuncture in Treatment of Simple Obesity in Animal Models: A Systematic Review and Meta-Analysis. (14th July 2019) - Fan, Xiao-lin; Yu, Mei-ling; Fu, Shu-Ping; Zhuang, Yi; Lu, Sheng-feng
Abstract : Background. Simple obesity has become a global risk to health of human beings. Acupuncture, as one of traditional Chinese medicine therapies, has been widely used in obesity treatment in recent years. However, the individual heterogeneity which makes acupuncture's efficiency unstable leads to some controversy. So more evidence-based results are necessary to judge the effectiveness of acupuncture in treatment of simple obesity. Compared with clinical trials, animal experiments are controllable, and the underlying mechanism is more likely to be explored. Last but not the least, more and more experimental studies on acupuncture for animal obesity have been published. Therefore, we conducted the systematic review and meta-analysis to evaluate the effectiveness of acupuncture in treating simple obesity in animal experiments. Methods. Randomized Controlled Trials (RCTs) on acupuncture for simple obesity animal models were searched from six databases: PubMed, MEDLINE, CNKI, VIP, WanFang Date, and CMB from inception to February 2017 and updated on April 12, 2019. RevMan 5.3 software was used for meta-analysis. Treatment effects were summarized as relative risk (RR) and Standard mean difference (SMD) with 95% of confidence interval (CI). Results. A total of 108 trials involving 5731 rats were included. Meta-analysis showed that acupuncture had better effect on reducing weight (SMD -2.60, 95%CI: -2.93 to -2.26, p<0.00001) and Lee's index (SMD -2.62, 95%CI:-3.18 to -2.06, p<0.00001) compared with control group. However, the methodological quality of included studies was generally poor. Details of blinding were not reported in most studies. In spite of high heterogeneity being observed on the merged data, sensitivity analysis using the leave-one-out approach, subgroup analysis based on different acupuncture techniques, and rat strains and meta-regression all failed to find the sources of heterogeneity. The asymmetric funnel plot suggested publication bias. Besides, adverse events were not reported in any reports. Conclusions. Our review provided positive evidence of acupuncture for simple obesity. Unfortunately, none of the firm conclusions can be drawn due to methodological flaws, high heterogeneity, and publication bias. More high-quality trials are needed in future to get objective conclusions.